Positive Effect of Konjac Glucomannan on Lowering Blood Pressure in Hypertensive Wistar Rats - Bryan Anggara Putra; Sugeng Mashudi; Alfia Pradita Sari; Fany Risma Afriani; Yaya Sulthon Aziz; Tukimin bin Sansuwito (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2024)
Hypertension is a non-communicable disease that is currently a top priority for global health. Commonly offered anti-hypertensive pharmacological therapies such as ACE-inhibitors are known to have side effects in long-term use, unlike herbal glucomannan, which has been used as a treatment for patients with type 2 diabetes. The purpose of this study was to see what effect applying glucomannan supplements for 6 hours had on blood pressure parameters obtained from the wistar rat subjects who had hypertension. Twenty five male Wistar rats with normal systolic blood pressure (sBP) ± 110 mmHg were involved in the study; they received a 10% high salt diet for 14 days. They were divided into 4 groups: the positive control group G1 received captopril at 25 mg/kg of body weight and the treatment groups G2  50 mg KGM. Blood pressure measurement using sphygmonanometers with diastolic blood pressure (dBP) is the exclusion criterion of the study. Data analysis is done with a paired sample t-test. Blood pressure in each group decreased after 6 hours of intervention, but the most significant results were obtained in the G5 group that received glucomannan 100 mg/kg bb. In conclusion, Glucomannan can lower blood pressure; this potential is the same as that of red ginger, which modulates the production of angiotensin-corventing enzymes.